Investigating The Psychopathy Shown by Emma in The Bad Seed Film by Rob Lowe - Ni Putu Eka Aristayanti; I Gusti Agung Sri Rwa Jayantini; Putu Nur Ayomi (Institut Pariwisata dan Bisnis Internasional, 2024)
A literary work can be converted into another format, for instance, a film. In filmmaking, the themes taken are derived from our depiction of life. Therefore, a film can raise a psychological theme that discusses one of gripping psychology like personality disorders. One of the personality disorders that often heard of is psychopathy. Through the characters in the film, a psychological perspective of a psychopath is displayed. This research aims to analyze the type of psychopathic behavior depicted by Emma Grossman as the main character in The Bad Seed (2018) film directed by Rob Lowe. The author used a qualitative method in describing the analysis of psychopathic behavior experienced by the main character. In investigating the type of psychopathy on Emma, the theory proposed by Millon and Davis (1998) was applied. Based on the research, Emma's enviousness which turns into revenge and several background personality of her psychopathy match the type of Malignant Psychopath. In addition, this research is expected to provide awareness of psychopathy behavior.